Cognitive-behavioral longitudinal assessment in ALS: the Italian Edinburgh Cognitive and Behavioral ALS screen (ECAS). Issue 5 (3rd July 2018) - Poletti, Barbara; Solca, Federica; Carelli, Laura; Faini, Andrea; Madotto, Fabiana; Lafronza, Annalisa; Monti, Alessia; Zago, Stefano; Ciammola, Andrea; Ratti, Antonia; Ticozzi, Nicola; Abrahams, Sharon; et al.
Abstract: Objective : The study presents data on the longitudinal administration of the Italian Edinburgh Cognitive and Behavioral ALS Screen (ECAS). We investigated cognitive-behavioral performance in a group of ALS patients over time and the feasibility of repeating the ECAS longitudinally compared with standard neuropsychological tests. Finally, correlations between clinical/genetic and cognitive/behavioral data were considered. Methods : One hundred and sixty-eight ALS patients were tested at baseline (T0 ). Among these, 48 patients performed the ECAS after 6 months (T1 ), 18 patients performed it at T2 (12 months), and five patients were assessed after 24 months (T3 ). Participants were also administered two cognitive test (FAB; MoCA) and psychological questionnaires (BDI; STAI/Y). The FBI was carried out with caregivers. Results : No cognitive deterioration was found across follow-ups. In contrast, although scores did not change between T0 and T1, scores improved significantly for ECAS Total/ALS Non-specific and Memory domains when the ECAS was repeated on three occasions (T0, T1, T2 ). Apathy/Inertia was the most common behavioral symptom, but no worsening of behavioral scores was detected over time. After 12–24 months, patients were still able to perform the ECAS in total, in contrast to FAB and MoCA, which were only partially administrable. Conclusions : The significant improvement of some ECAS scores over time supports the presence of possible practice effects, particularly in the memory domain, highlighting the need to accommodate for these in longitudinal assessments, through healthy controls groups or alternate versions. This work represents the first Italian ECAS follow-up study and confirms ECAS feasibility in patients with increasing physical disability.